Characteristics and Long-Term Ablation Outcomes of Supraventricular Arrhythmias in Hypertrophic Cardiomyopathy: A 10-Year, Single-Center Experience - Zhang, Hong-Da; Ding, Lei; Weng, Si-Xian; Zhou, Bin; Ding, Xiao-Tong; Hu, Li-Xing; Qi, Ying-Jie; Yu, Feng-Yuan; Feng, Tian-Jie; Zhang, Jing-Tao; Fang, Pi-Hua; Hua, Wei; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: A variety of supraventricular arrhythmias (SVAs) may occur in patients with hypertrophic cardiomyopathy (HCM). The characteristics and long-term ablation outcomes of different types of SVAs in HCM have not been comprehensively investigated. Methods: We retrospectively enrolled 101 consecutive patients with HCM who were referred to the electrophysiology and arrhythmia service from May 2010 to October 2020. The clinical features and ablation outcomes were analyzed. Results: Seventy-eight patients had SVAs, which comprised 50 (64.1%) cases of atrial fibrillation (AF), 16 (20.5%) of atrial flutter (AFL), 15 (19.2%) of atrioventricular reentrant tachycardia (AVRT), 11 (14.1%) of atrial arrhythmia (AT), and 3 (3.8%) of atrioventricular nodal reentrant tachycardia (AVNRT). Thirty-four patients underwent catheter ablation and were followed up for a median (interquartile range) of 58.5 (82.9) months. There was no recurrence in patients with non-AF SVAs. In patients with AF, the 1- and 7-year AF-free survival rates were 87.5 and 49.5%, respectively. A receiver operator characteristic analysis showed that a greater left ventricular end-diastolic dimension (LVEDD) was associated with a higher recurrence of AF, with an optimum cutoff value of 47 mm (c-statistic = 0.91, p = 0.011, sensitivity = 1.00, specificity = 0.82). In Kaplan–Meier analysis, patients with a LVEDD ≥ 47 mm had worse AF-free survival than those with a LVEDD <47 mm (log-rank p = 0.014). Conclusions: In this unique population of HCM, AF was the most common SVA, followed in order by AFL, AVRT, AT, and AVNRT. The long-term catheter ablation outcome for non-AF SVAs in HCM is satisfactory. A greater LVEDD predicts AF recurrence after catheter ablation in patients with HCM.